PEMBINAAN BLOGGING PADA MASYARAKAT SEKUPANG BATAM KEPULAUAN RIAU - Pastima Simanjuntak; Erlin Elisa; Nurma Dhona Handayani (STMIK Royal, 2020)
Abstract: Along with advances in information technology that is increasingly changing and encouraging various efforts to change, where the Sei Harapan Sekupang community is still unfamiliar with information and communication technology, many people, especially school children and adolescents who still do not understand the application of information technology in the field of blogging and also still lack of understanding of the application of ICT, especially applications that are on the computer, therefore the purpose of this coaching is to invite the Sei Harapan community to find out the use of information technology in the field of Blogging. This blogging coaching is also to find out the latest technology and information that is currently growing rapidly including blogging and know the benefits of information technology development in the field of blogging so that the public can be motivated to evaluate and learn information technology in the field of blogging as a basis for learning and to support various activities in daily life are included in online sales activities using blogs, and are accustomed to using information technology tools appropriately and optimally to obtain and process information in learning, working and other activities so that the community is able to be creative, develop imaginative attitudes, develop independent exploration capabilities , and easy to adapt to new developments in the environment. Keywords: Coaching, Training, Applications, Blogging Abstrak: Seiring dengan kemajuan teknologi informasi yang semakin mengalami perubahan dan mendorong berbagai usaha perubahan, dimana masyarakat Sei Harapan Sekupang masih awam tentang teknologi informasi dan komunikasi, banyaknya masyarakat khususnya anak-anak sekolah dan remaja yang masih belum paham akan penerapan teknologi informasi dibidang blogging dan juga masih kurang paham akan penerapan TIK khususnya aplikasi yang ada di komputer, maka dari itu tujuan pembinaan ini mengajak masyarakat Sei Harapan untuk mengetahui pemanfaatan teknologi informasi dibidang Blogging. Pembinaan blogging ini juga untuk mengetahui teknologi dan informasi terbaru yang saat ini berkembang dengan pesat termasuk blogging dan mengetahui manfaat perkembangan teknologi informasi dibidang blogging sehingga masyarakat dapat termotivasi untuk mengevaluasi dan mempelajari teknologi informasi dibidang blogging sebagai dasar untuk belajar dan untuk mendukung berbagai aktifitas dalam kehidupan sehari-hari termasuk dalam hal aktivitas penjualan secara online dengan menggunakan blog, dan terbiasa menggunakan perangkat teknologi informasi secara tepat dan optimal untuk mendapatkan dan memproses informasi dalam kegiatan belajar, bekerja, dan aktifitas lainnya sehingga masyarakat mampu berkreasi, mengembangkan sikap imaginatif, mengembangkan kemampuan eksplorasi mandiri, dan mudah beradaptasi dengan perkembangan baru di lingkungannya. Kata kunci: Pembinaan, Pelatihan, Aplikasi, Blogging